2006
DOI: 10.1155/2007/185364
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Alkylaromatics

Abstract: Hydroperoxide atα-position to the aromatic ring is the primary oxidation product formed. In all cases monoalkylbenzenes lead to the formation of benzoic acid. Oxidation in the presence of transition metal salts not only accelerate but also selectively decompose the hydroperoxides. Alkyl naphthalenes mainly produce the corresponding naphthalene carboxylic acids. Hock-rearrangement by the influence of strong acids converts the hydroperoxides to hemiacetals. Peresters formed from the hydroperoxides undergo Criege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The main products of oxidation of di-and poly-alkylbenzenes are generated via a hydroperoxide pathway which goes on to produce aryl alcohols and aryl aldehydes and ketones. These can go on to be oxidised to the corresponding aryl acid [26]. Detailed GCMS analysis of the aromatics post oxidation in the PetroOxy supports at least the first part of this proposal, however no acids were found in any of the post PetroOxy samples.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The main products of oxidation of di-and poly-alkylbenzenes are generated via a hydroperoxide pathway which goes on to produce aryl alcohols and aryl aldehydes and ketones. These can go on to be oxidised to the corresponding aryl acid [26]. Detailed GCMS analysis of the aromatics post oxidation in the PetroOxy supports at least the first part of this proposal, however no acids were found in any of the post PetroOxy samples.…”
Section: Resultsmentioning
confidence: 61%
“…It has been shown that the isopropyl group of p-cymene is oxidised in preference to the methyl group and that oxidation of an alkyl benzene normally produces the corresponding carbonyl compound via a hydroperoxide formed at the alpha position on the aromatic ring [26,31]. The reactivity of the alpha-methynic hydrogen for cymene has been compared to that of toluene at ratio of 4.1:1 at 85°C [32], albeit metal-catalysed.…”
Section: P-cymene Blending -Induction Timesmentioning
confidence: 99%
“…In a neutral medium at high temperatures, as already mentioned, the process proceeds by a radical mechanism. Studies based on individual hydrocarbons , show that primary hydroperoxides mainly decompose to form acids; secondaryalcohols, ketones, acids, and hydrocarbons; tertiaryalcohols (phenols) and acetone.…”
Section: Resultsmentioning
confidence: 99%
“…According to [17] CdSe nanoparticles modified with benzoic acid interact with xylene (toluene) from causing a change of their optical properties. In our electrolyte, a strong oxidizing medium was created in which impurities of an aromatic carboxylic acid, isomers of the toluic acid [34] and its radicals (toluic aldehyde and xylene hydroperoxide) [35,36] are formed due to the presence of hydrochloric and nitric acids and the temperature of 95°C. Toluic acid as well as benzoic acid is a substance which interacts with the surface of the nanoparticles via the carboxyl groups to form micellar structures.…”
Section: Resultsmentioning
confidence: 99%